A Parametric Modelling Method for Dexterous Finger Reachable Workspaces. (17th March 2016) - Yang, Wenzhen; Jin, Zhongzheng; Wu, XingLi; Chen, Guanwen; Pan, Zhigeng; Zhu, Zhichao
The well-known algorithms, such as the graphic method, analytical method or numerical method, have some defects when modelling the dexterous finger workspace, which is a significant kinematical feature of dexterous hands and valuable for grasp planning, motion control and mechanical design. A novel modelling method with convenient and parametric performances is introduced to generate the dexterous-finger reachable workspace. This method constructs the geometric topology of the dexterous-finger reachable workspace, and uses a joint feature recognition algorithm to extract the kinematical parameters of the dexterous finger. Compared with graphic, analytical and numerical methods, this parametric modelling method can automatically and conveniently construct a more vivid workspace's forms and contours of the dexterous finger. The main contribution of this paper is that a workspace-modelling tool with high interactive efficiency is developed for designers to precisely visualize the dexterous-finger reachable workspace, which is valuable for analysing the flexibility of the dexterous finger.